ADAR1-Mediated RNA Editing and Its Role in Cancer - Liu, Jizhe; Wang, Fei; Zhang, Yindan; Liu, Jingfeng; Zhao, Bixing (Frontiers in Cell and Developmental Biology, 2022)
It is well known that the stability of RNA, the interaction between RNA and protein, and the correct translation of protein are significant forces that drive the transition from normal cell to malignant tumor. Adenosine deaminase acting on RNA 1 (ADAR1) is an RNA editing enzyme that catalyzes the deamination of adenosine to inosine (A-to-I), which is one dynamic modification that in a combinatorial manner can give rise to a very diverse transcriptome. ADAR1-mediated RNA editing is essential for survival in mammals and its dysregulation results in aberrant editing of its substrates that may affect the phenotypic changes in cancer. This overediting phenomenon occurs in many cancers, such as liver, lung, breast, and esophageal cancers, and promotes tumor progression in most cases. In addition to its editing role, ADAR1 can also play an editing-independent role, although current research on this mechanism is relatively shallowly explored in tumors. In this review, we summarize the nature of ADAR1, mechanisms of ADAR1 editing-dependent and editing-independent and implications for tumorigenesis and prognosis, and pay special attention to effects of ADAR1 on cancers by regulating non-coding RNA formation and function.